2023
DOI: 10.29333/ejmste/12951
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mathematics learning environment supported by error-analysis activities on classroom interaction

Abstract: This study was designed to investigate the effect of mathematics learning environment supported by error-analysis activities on classroom interaction. To achieve this purpose, two classes of seventh grade students (aged 12-13 years) were randomly selected and were assigned into two groups; experimental (number of student=24) and control (number of students=24). The experimental group was exposed to error-analysis activities, whereas the control group studied the same mathematics content without any error-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Based on the very high motivation level of the respondents to the study, the findings of the first question emphasize the role of intrinsic motivation in directing student teachers to participate in professional development programs. This finding is in line with previous studies [49,50], which confirmed that intrinsic motivation positively impacts student teachers' participation in professional development programs.…”
Section: -Discussionsupporting
confidence: 93%
“…Based on the very high motivation level of the respondents to the study, the findings of the first question emphasize the role of intrinsic motivation in directing student teachers to participate in professional development programs. This finding is in line with previous studies [49,50], which confirmed that intrinsic motivation positively impacts student teachers' participation in professional development programs.…”
Section: -Discussionsupporting
confidence: 93%
“…By addressing these gaps, this study aims to contribute to the literature on attitudes towards Mathematics and Mathematics performance, while also providing insights that can inform educational practice and policy. Figure 1 shows the conceptual model that elucidates the interrelationship between attitude toward Mathematics (Garzon & Casinillo, 2021) and Mathematics achievement and the mediating role of self-efficacy (Casinillo, 2023), parental support (Casinillo et al, 2023), and the moderating effect of the learning environment (Khasawneh et al, 2023).…”
Section: Theoretical Basismentioning
confidence: 99%
“…Based on the importance of mathematics teachers' knowledge, and the significance of training them to be effective teachers in mathematics learning environments, research studies were conducted on conceptual understanding and pedagogical knowledge of mathematics teachers, as separate variables, around the world and in Jordan (Al-Barakat et al, 2022a;Al-Hassan et al, 2012;Al-Tarawneh, 2019;Bwalya & Rutegwa, 2023;Fraihat et al, 2022;Khasawneh et al, 2023;Mapulanga et al, 2022;Meier, 2021;Shaqar, 2020).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Khasawneh et al (2022) emphasized that one of the sources of support for teachers' pedagogical knowledge in mathematics is the experiences that each of them possesses. In addition, Khasawneh et al (2023) indicated that the classroom teaching practices of the mathematics teacher are a major indicator and determinant of students' behavior in the classroom, their progress and academic achievement. In this regard, Hill et al (2008) emphasized the need to link PCK with student learning outcomes, the ability to know perceptions and prior knowledge they possess, and that professional development opportunities focus on developing teacher knowledge and skills in understanding students' work and their mathematical thinking NCTM (2014) stresses that the ability of teachers to keep pace with the requirements of development, and to deal with them, constitutes a challenge to the reform process, as it can only be achieved if teachers have a deep understanding of mathematics and the ability to deal with it flexibly during the process of their teaching.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation